Validation of Malay version of emotion thermometer among adult victims of flood disaster in Kelantan - Zahidi, Zaidatul-Zarina Mohd Zahidi (2017)
Background: Emotion Thermometer is a quick visual analogue scale in assessing emotional distress originally designed for cancer patients. To date, there is no visual analogue scale available for quick assessment of emotional distress post disaster. Aim: This study aimed to validate the Malay version of Emotion Thermometers in flood disaster survivors in Kelantan. Methods: A cross-sectional study, involving 150 participants who were involved in flood disaster in the Kuala Krai district, was conducted from April 2015 to June 2015. The sample selection was done by multistage sampling method. Back to back translation, content validity and face validity processes were conducted by a group of expert, followed by pilot study. The final version of the questionnaire then was used for the validation study. The data analyses involve assessment of correlation by comparing Malay Emotion Thermometer (MET) with Malay version of Depression, Anxiety and Stress Scale 21 (DASS-M 21) by using R software. Results: Domains of depression, anxiety and distress of MET correlated well with respective domains of DASS-M 21. Pearson‘s correlations, r ranged from 0.25 to 0.34. All domains showed good sensitivities and acceptable area under the curve values. At theoptimal cut-off scores of >2 for distress, >3 for anxiety and >1 for depression, the sensitivity were 0.66, 0.78, and 0.79 respectively. Conclusion: This study demonstrates that The Malay version of Emotion Thermometer can be used in identifying emotional distress during traumatic event. To improve the validity of this screening tool, further consideration to overcome the limitation should be done so that a valid, reliable, fast and easy screening tool can be achieved.